An insight into polishing slurry for high quality and efficiency polishing of diamond. (October 2022) - Yuan, Song; Guo, Xiaoguang; Li, Ming; Jin, Zhuji; Guo, Dongming
Abstract: Oxidants occupy a decisive role in the final surface quality and remove rate during chemical mechanical polishing (CMP). As for diamond, it is still a huge challenge to achieve high quality and efficiency removal. Herein, a new polishing slurry is provided based on Fenton reaction. The SEM results show that the snowflake oxide layer appears on the diamond surface after corrosion, and the sub-nanometer morphology of Sa= 0.076 nm, Sq= 0.097 nm, Sz= 3.472 nm and the remove rate of 752 nm/h are obtained after CMP. The CO or C-OH groups adsorbed on the diamond surface is the reason that achieve the high efficiency removal. This study provides a new polishing slurry for the high quality and efficiency CMP of diamond.